2010
DOI: 10.4097/kjae.2010.58.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infusion rate and catheter length on the temperature of warming fluid

Abstract: BackgroundWe used warming fluid for maintenance of body temperature in operating room or intensive care unit. This study was aimed to investigate the effect of infusion rate and catheter length on the temperature of warming fluid.MethodsNormal saline was used for testing infusion and temperature of infusion was maintained by a warmer as 40℃. The temperatures of solution in infusion line were measured at 0, 25, 50, 75, and 100 cm apart from warmer at six different flow rates (100, 200, 300, 700, 1,400, and 2,10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…The final delivered fluid temperature was decreased significantly through increase in the length of the extended tube [15,22,23], despite some fluid warmers being able to warm the intravenous fluid up to 37 o C [12,14]. At low and moderate flow rates, the ThermoSens, the Ranger, and other warmers with similar technology could not deliver normothermic fluid (37 o C) at a tubing distance greater than 75 cm [24][25][26]. The Mega Acer Kit was also unsuccessful in delivering fluid temperatures greater than 35 o C above a tubing distance of 75 cm at 300-1,000 mL/h [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The final delivered fluid temperature was decreased significantly through increase in the length of the extended tube [15,22,23], despite some fluid warmers being able to warm the intravenous fluid up to 37 o C [12,14]. At low and moderate flow rates, the ThermoSens, the Ranger, and other warmers with similar technology could not deliver normothermic fluid (37 o C) at a tubing distance greater than 75 cm [24][25][26]. The Mega Acer Kit was also unsuccessful in delivering fluid temperatures greater than 35 o C above a tubing distance of 75 cm at 300-1,000 mL/h [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…ThermoSens® warms the fluid using a heating tube containing a heating plate, in direct contact with the fluid [ 13 ]. FloTem and JOYOTHER BM-1 (Joyother, Seoul, Korea) also employ the dry heat technology for warming the fluid with a tube heated by electric heater elements, similar to technology of ThermoSens® [ 11 17 ]. WarmFlo® heats the fluid using a dry cassette heat exchange technology, similar to Ranger™, which employs dry heat technology using a counter-current metal heating plate [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…FloTem, with a disposable length of 108 cm, requires a flow rate of at least 300 ml/h to deliver fluid at temperatures above 32℃; however, it could not deliver fluid above 35℃, even when the flow rate was increased to 1,000 ml/h [ 6 ]. JOYOTHER BM-1 was not effective in delivering the warmed fluid at a distance greater than 75 cm from the outlet of the device at low and moderate flow rates [ 17 ]. Patel et al [ 11 ] also showed that FloTem delivered warmed fluid with a temperature of 29.5℃ at 390 ml/h and 30.8℃ at 780 ml/h, similar to the result of this study (29.93 [29.59–30.27]℃) using ThermoSens®.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of this study will serve as a baseline for future clinical studies. Lee et al [ 15 ] suggested that both the flow rate and length of the catheter from the warmer outlet to the patient influence the effectiveness of the warmer. A longer catheter may be associated with more heat loss to the ambient; thus, the outlet fluid should be located as close as possible to the patient.…”
Section: Additional Pointsmentioning
confidence: 99%